The Misallocation of Finance - WHITED, TONI M.; ZHAO, JAKE (Journal of Finance, 2021)
ABSTRACT We estimate real losses arising from the cross‐sectional misallocation of financial liabilities. Extending a production‐based framework of misallocation measurement to the liabilities side of the balance sheet and using manufacturing firm data from the United States and China, we find significant misallocation of debt and equity in China but not the United States. Reallocating liabilities of firms in China to mimic U.S. efficiency would produce gains of 51% to 69% in real value‐added, with only 17% to 21% stemming from inefficient debt‐equity combinations. For Chinese firms that are large or in developed cities, we estimate lower distortionary financing costs.